(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2020)
We describe the case of a patient with refractory post-operative conversion disorder successfully treated with electroconvulsive therapy (ECT) with good clinical outcome. A 66-year-old Caucasian male presented to the emergency department (ED) with altered mental status and was nonverbal three days after undergoing an uncomplicated incisional hernia repair. He had a past medical history of major depression with psychotic features and generalized anxiety disorder as well as a kidney transplant. He had multiple previous psychiatric hospitalizations in the 1980s for severe depression with suicidality treated successfully with ECT. The patient was admitted, and a diagnosis of conversion disorder was made. His condition deteriorated over 21 days of inpatient management and he failed to respond to methylphenidate, aripiprazole, haloperidol, and lorazepam. Bilateral ECT treatment was initiated and the patient demonstrated a dramatic functional improvement after the first treatment. He was discharged home after receiving 6 total treatments and continued outpatient treatments with good clinical outcome. ECT may be considered in patients with refractory conversion disorder with a previous history of successful treatment.